(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The present article provides an analysis of A Diplomat’s Wife, written by Edith Coues, Nelson O’Shaughnessy’s wife, who was in charge of business issues at the North American Embassy in Mexico from October 1911 to May 1914. This work, which is an extraordinarily rich source of information on the history of diplomacy and international relations, especially between Mexico and the USA, allows us to understand Edith’s interpretation of events as she was both an observer and a participant of historical and social processes in the diplomatic world during the Huerta dictatorship. In order to understand the complexity of the text, our perspective focuses more on the publication rather than on the author. The analysis comprises three approches which privilege the internalist perspective.